Ultrasensitive Anomalous Hall Effect in Ta/CoFe/Oxide/Ta Multilayers - Guang Yang; Yongye Li; Xi Chen; Jingyan Zhang; Guanghua Yu (Advances in Condensed Matter Physics)
Ultrahigh anomalous Hall sensitivity has been demonstrated in Ta/CoFe/Oxide/Ta multilayers. By changing oxides (MgO and HfO2) and annealing temperature, different annealing dependence of sensitivity was found in MgO-sample and HfO2-sample. For the MgO-sample, the anomalous Hall sensitivity reaches 18792 Ω/T in the as-deposited state and significantly reduces as annealing temperature increases. On the contrary, the sensitivity of the as-deposited HfO2-sample is only 765 Ω/T, while it remarkably increases with annealing temperature increasing, finally reaching 14741 Ω/T at 240°C. The opposite variation of anomalous sensitivity in two samples originates from the different change of magnetic anisotropy and anomalous Hall resistance during the annealing process. Our study provides a new perspective that both the choice of oxide material and the optimization of annealing treatment are important to the anomalous Hall sensitivity.